Comparison of Neuropsychological and Balance Performance Validity Testing. Issue 2 (4th March 2017) - Armistead-Jehle, Patrick; Lange, Beth J.; Green, Paul
ABSTRACT: Performance validity testing in the context of neuropsychological assessment is well established. While such measures are also available with balance testing, little research has investigated these two domains in concert. The purpose of this study was to compare scores on two measures of performance validity across cognitive and balance modalities. Seventy-eight subjects independently evaluated by a neuropsychologist and an otolaryngologist in the context of disability evaluations were administered the Word Memory Test and Computerized Dynamic Posturography. Results of the measures were significantly correlated ( r φ = 0.35, p = .002) and demonstrated 70.5% agreement. These data suggest that if symptom exaggeration occurs within one modality, other modalities may also be exaggerated and should be independently evaluated.